Semi-discretization method for solving boundary value problems for parabolic systems - Abdurazakov Abdujabbor; Mahmudova Nasiba; Mirzamahmudova Nilufar (Zien Journals, 2022)
This article discusses the propagation of heat in a three-layer plate. To solve problems, a combination of differential sweeps is used.
Keywords: Heat Propagation; Three-Layer Plate; Differential Equations; Differential Sweep